Perhitungan Pendanaan Program Pensiun Manfaat Pasti dengan Metode Benefit Prorate Tipe Constan Dollar - Putri, Eka Wahyuni; Muchlian, Melvi; Z, Yulia Rahmawati (AKTUARIA, 2023)
This study discusses the calculation of pension funding using the constant dollar type prorate benefit method which is influenced by the basic salary class and length of service based on an interest rate of 3.50%, a salary increase rate of 6% per year, the percentage of pension benefits is 4.75% and based on tables Indonesian mortality in 2019 specifically for women which is influenced by interest rate factors. Normal pension contributions (premiums) can be determined based on theinitial annuity for life and the present value of pension benefits based on the last salary a year before entering retirement age. Based on the calculations that have been made from the calculation of the three salary assumptions, the value of the last year's assumed salary is greater than the last n years' average assumption and the average salary assumption while working. And it can be concluded that the amount of pension benefits received by employees with 35 years of service is greater than employees who work with 33 years of service. Because the longer an employee works, the greater the benefits he will receive. Likewise, the normal contributions paid annually using the constant dollar prorate benefit method are obtained with a length of service of 35 years, the premium paid will be greater than the length of service of 33 years. Because the longer a person works, the greater the premium paid and the higher the class level owned by the employee, the greater the premium that will be paid annually. Keywords : Pension Fund, Defined Benefit, Benefit Prorate Method, Constant Dollar